Relationship between academic stress and cyberloafing behavior among Psychology Department Students at Universitas Pendidikan Indonesia - Hildan Hibrian; MIF Baihaqi; Helli Ihsan (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2021)
This study aims to determine the relationship between academic stress and cyberloafing among psychology department students at Universitas Pendidikan Indonesia (UPI). This correlational study involved 150 students recruited using the quota sampling technique. Academic Stress Inventory and The Cyberloafing Scale were employed as the data collection instrument. The obtained data were analyzed using product moment correlation analysis, showing a positive relationship between academic stress and cyberloafing. The results of the study can serve as a reference for school counselors in designing guidance and counseling services to reduce academic stress and cyberloafing.